Wine Spoilage Control: Impact of Saccharomycin on Brettanomyces bruxellensis and Its Conjugated Effect with Sulfur Dioxide - Branco, Patricia (2022)
ABSTRACT: The yeast Brettanomyces bruxellensis is one of the most dangerous wine contaminants due to the production of phenolic off-flavors such as 4-ethylphenol. This microbial hazard is regularly tackled by addition of sulfur dioxide (SO2). Nevertheless, B. bruxellensis is frequently found at low levels (ca 10(3) cells/mL) in finished wines. Besides, consumers health concerns regarding the use of sulfur dioxide encouraged the search for alternative biocontrol measures. Recently, we found that Saccharomyces cerevisiae secretes a natural biocide (saccharomycin) that inhibits the growth of different B. bruxellensis strains during alcoholic fermentation. Here we investigated the ability of S. cerevisiae CCMI 885 to prevent B. bruxellensis ISA 2211 growth and 4-ethylphenol production in synthetic and true grape must fermentations. Results showed that B. bruxellensis growth and 4-ethylphenol production was significantly inhibited in both media, although the effect was more pronounced in synthetic grape must. The natural biocide was added to a simulated wine inoculated with 5 x 10(2) cells/mL of B. bruxellensis, which led to loss of culturability and viability (100% dead cells at day-12). The conjugated effect of saccharomycin with SO2 was evaluated in simulated wines at 10, 12, 13 and 14% (v/v) ethanol. Results showed that B. bruxellensis proliferation in wines at 13 and 14% (v/v) ethanol was completely prevented by addition of 1.0 mg/mL of saccharomycin with 25 mg/L of SO2, thus allowing to significantly reduce the SO2 levels commonly used in wines (150-200 mg/L).